2016
DOI: 10.1371/journal.pone.0159375
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Elovl6 in Chondrocyte Growth and Differentiation during Growth Plate Development in Mice

Abstract: ELOVL family member 6, elongation of very long chain fatty acids (Elovl6) is a microsomal enzyme, which regulates the elongation of C12-16 saturated and monounsaturated fatty acids. Elovl6 has been shown to be associated with various pathophysiologies including insulin resistance, atherosclerosis, and non-alcoholic steatohepatitis. To investigate a potential role of Elovl6 during bone development, we here examined a skeletal phenotype of Elovl6 knockout (Elovl6-/-) mice. The Elovl6-/- skeleton was smaller than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…ELOVL6 extends the carbon chain of fatty acids and inhibits their use, which may be detrimental in rapid tumor proliferation. Additional studies have confirmed that ELOVL6 is involved in both migration and proliferation (45,46), and in the present study, ELOVL6 expression was associated with vascular invasion, which is also closely associated with factors such as vascular endothelial growth factor. The majority of chronic liver diseases are associated with hypoxic symptoms that come with with metabolic diseases, such as non-alcoholic fatty liver disease.…”
Section: Univariate Analysis Multivariate Analysis ------------------supporting
confidence: 86%
“…ELOVL6 extends the carbon chain of fatty acids and inhibits their use, which may be detrimental in rapid tumor proliferation. Additional studies have confirmed that ELOVL6 is involved in both migration and proliferation (45,46), and in the present study, ELOVL6 expression was associated with vascular invasion, which is also closely associated with factors such as vascular endothelial growth factor. The majority of chronic liver diseases are associated with hypoxic symptoms that come with with metabolic diseases, such as non-alcoholic fatty liver disease.…”
Section: Univariate Analysis Multivariate Analysis ------------------supporting
confidence: 86%
“…However, because Elovl6 deletion was not targeted to the pancreas and was achieved in all tissues, the possibility remains that Elovl6 deletion might affect the FA profile in other tissues to affect overall organismal metabolism and, therefore, b-cell function. Indeed, we previously showed that Elovl6 deficiency altered FA composition in serum and various organs and affected a wide range of cellular functions and the disease progression (19,21,(48)(49)(50). We assume the changes of plasma FA composition might influence the FA composition of islets; however, changes in FA composition of db/db;Elovl6 2/2 islets were different from changes observed in plasma: a marked reduction in oleate component without a reduction in stearate and an increase in palmitate, compared with db/db;Elovl6 +/+ islets.…”
Section: Discussionmentioning
confidence: 99%
“…Elovl6 knockout mice are insulin resistant and develop obesity and hepatosteatosis when fed a high fat diet (Matsuzaka et al, 2007), indicating that ELOVL6 is important to normal metabolic regulation. The activity of ELOVL6 can also regulate thermogenic activity in brown fat adipocytes (Tan et al, 2015) and chondrocyte growth (Kikuchi et al, 2016). No direct causal linkage of ELOVL6 mutations to human disease has been established.…”
Section: Introductionmentioning
confidence: 99%